Adjuvant chemotherapy in early-stage endometrioid endometrial cancer with >50% myometrial invasion and negative lymph nodes. Issue 4 (19th February 2021) - Multinu, Francesco; Garzon, Simone; Weaver, Amy L; McGree, Michaela E.; Sartori, Enrico; Landoni, Fabio; Zola, Paolo; Dinoi, Giorgia; Aletti, Giovanni; Block, Matthew S; Gadducci, Angiolo; Mariani, Andrea
Abstract : Objective: The role of adjuvant chemotherapy as an addition or alternative to radiotherapy for early-stage high-risk endometrioid endometrial cancer is controversial. This study aimed to investigate the role of adjuvant chemotherapy in early-stage high-risk endometrioid endometrial cancer. Methods: We identified patients with stage I or II endometrioid grade 2 or 3 endometrial cancer with myometrial invasion >50% and negative lymph nodes after pelvic with or without para-aortic lymphadenectomy at four institutions (USA and Italy). Associations between chemotherapy and cause-specific and recurrence-free survival were assessed with Cox proportional hazards models. Hematogenous, peritoneal, and lymphatic recurrences were defined as 'non-vaginal'. Results: We identified 329 patients of mean (SD) age 66.4 (9.8) years. The median follow-up among those alive was 84 (IQR 44–133) months. The 5-year cause-specific survival was 86.1% (95% CI 82.0% to 90.4%) and the 5-year recurrence-free survival was 82.2% (95% CI 77.9% to 86.8%). Stage II (vs stage IB) was associated with poorer cause-specific and recurrence-free survival. A total of 58 (90.6%) of 64 patients who had chemotherapy had 4–6 cycles of platinum-based regimen. In adjusted analysis, we did not observe a statistically significant improvement in cause-specific survival (HR 0.34; 95% CI 0.11 to 1.03; p=0.06) or non-vaginal recurrence-free survival (HR 0.36; 95% CI 0.12 to 1.08; p=0.07) with adjuvant chemotherapy. Sixteen of 18 lymphatic recurrences (88.9%; 3/5 pelvic, all 13 para-aortic) were observed in the 265 patients who did not receive adjuvant chemotherapy. Among stage II patients, no deaths (100% 5-year recurrence-free survival) were observed in the eight patients who received adjuvant chemotherapy compared with 66% 5-year recurrence-free survival in the 34 patients who did not. Conclusion: Although we observed that adjuvant chemotherapy was associated with improved oncologic outcomes in early-stage high-risk endometrioid endometrial cancer, the associations did not meet conventional levels of statistical significance. Further research is warranted in this relatively uncommon subgroup of patients.